2018
DOI: 10.3390/ijms19030837
|View full text |Cite
|
Sign up to set email alerts
|

Combined Subchronic Toxicity of Aluminum (III), Titanium (IV) and Silicon (IV) Oxide Nanoparticles and Its Alleviation with a Complex of Bioprotectors

Abstract: Stable suspensions of metal/metalloid oxide nanoparticles (MeO-NPs) obtained by laser ablation of 99.99% pure elemental aluminum, titanium or silicon under a layer of deionized water were used separately, or in three binary combinations, or in a ternary combination to induce subchronic intoxications in rats. To this end, the MeO-NPs were repeatedly injected intraperitoneally (i.p.) 18 times during 6 weeks before measuring a large number of functional, biochemical, morphological and cytological indices for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 58 publications
1
20
0
2
Order By: Relevance
“…As follows from Table 1 (which presents mostly those indices for which the exposed group differed from the controls statistically significantly), even though the total exposure period was short, certain functional effects of toxic action did manifest themselves. We noted the following: an increase in liver mass typical of subchronic and chronic intoxications with practically all metal-oxide nanoparticles ever studied by us;elevated release of lactate dehydrogenase in the blood due, probably, to the toxic damage to the liver cells and to the pulmonary macrophages;leukocytosis;systemic inhibition of the oxidation-reduction energy metabolism, the integrated cytochemical indicator of which is the suppression of succinate dehydrogenase activity in blood lymphocytes, which we repeatedly observed in experiments involving practically any of the toxic metals in any form [23,26,27,28];enhanced lipid peroxidation judging by the increased concentration of malondialdehyde in the blood;stimulation of erythropoiesis suggested by an increase in the erythrocyte count (along with an increased proportion of reticulocytes), hematocrit, and hemoglobin content of the blood.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…As follows from Table 1 (which presents mostly those indices for which the exposed group differed from the controls statistically significantly), even though the total exposure period was short, certain functional effects of toxic action did manifest themselves. We noted the following: an increase in liver mass typical of subchronic and chronic intoxications with practically all metal-oxide nanoparticles ever studied by us;elevated release of lactate dehydrogenase in the blood due, probably, to the toxic damage to the liver cells and to the pulmonary macrophages;leukocytosis;systemic inhibition of the oxidation-reduction energy metabolism, the integrated cytochemical indicator of which is the suppression of succinate dehydrogenase activity in blood lymphocytes, which we repeatedly observed in experiments involving practically any of the toxic metals in any form [23,26,27,28];enhanced lipid peroxidation judging by the increased concentration of malondialdehyde in the blood;stimulation of erythropoiesis suggested by an increase in the erythrocyte count (along with an increased proportion of reticulocytes), hematocrit, and hemoglobin content of the blood.…”
Section: Resultsmentioning
confidence: 87%
“…systemic inhibition of the oxidation-reduction energy metabolism, the integrated cytochemical indicator of which is the suppression of succinate dehydrogenase activity in blood lymphocytes, which we repeatedly observed in experiments involving practically any of the toxic metals in any form [23,26,27,28];…”
Section: Resultsmentioning
confidence: 91%
“…Two other studies have investigated the genotoxic potential of Al 2 O 3 NMs after intraperitoneal administration. These have demonstrated DNA damage in blood after 6 weeks of repeated exposure at 1.25 mg/kg bw [40] and in the brains of rats 48 h after a single intraperitoneal administration of Al 2 O 3 NMs, although at very high doses (from 4 to 8.5 g/kg bw) which were evaluated as lethal (from 30 to 65% of the LD50) in the same study [41]. In this study, the DNA damage was correlated with Al accumulation in several organs, including the brain.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing experimental data with the help of the model function (3), we discovered 22-36 some general principles, which were observed in all these experiments and which we believe to be representative of some important general patterns in combined toxicity, namely:The combined toxicity type depends on the effect by which it is assessed.The combined toxicity type depends on the choice of effect level.The combined toxicity type depends on the dose ratio of the toxic agents in the combination.Identification of the combined toxicity type in a certain region of dose combinations may reveal an opposite action of the toxicants.…”
Section: Introductionmentioning
confidence: 85%
“…In a series of publications, 22-36 model (3) was used by us for analyzing the combined toxicities of various substances. It was shown that this model enables one to describe both the unidirectional action types (additivity, subadditivity, superadditivity) and oppositely directed actions of toxic agents in a certain region of experimental dose combinations.…”
Section: Introductionmentioning
confidence: 99%